The Efficiency of Gas-Kinetic BGK scheme for solving 2-d compressible inviscid regular shock reflection problem - Ong, Jiunn Chit; Omar, Ashraf Ali; Asrar, Waqar; Hamdan, Megat M. (2004)
In this paper, the 1st and 2nd order gas-kinetic BGK scheme is developed and tested for its ability in solving the two-dimensional compressible inviscid flow fields. The BGK (Bhatnagar-Gross-Krook) scheme uses the collisional Boltzmann equation as the governing equation for flow evolutions. Second-order BGK scheme is also developed for flow simulation. This is achieved by means of reconstructing the initial data via MUSCL (Monotone Upstream-Centered Schemes for Conservation Laws) method. In addition, a multisage TVD (Total Variation Diminishing) Runge-Kutta method is employed for the time integration of the finite volume gas-kinetic scheme. A typical two-dimensional regular reflection of an oblique shock wave from a solid surface is chosen for testing the accuracy and robustness of the BGK scheme. The computational results are validated against the numerical results of Roe’s scheme.